Raptor - a sokol graphic novel ebook - McKean, Dave (Raptor., 2021)
A visual tour-de-force graphic novel from artist and writer Dave McKean (Black Dog, The Sandman).The Raptor, Sokol, flickers between two worlds: a feudal fantastical landscape where he must hunt prey to survive, and Wales in the late 1800s where a writer of supernatural tales mourns the passing of his young wife. He exists between two states, the human and the hawk. He lives in the twilight between truth and lies, life and death, reality and the imagination.World Fantasy, Harvey, British Science Fiction Association, and V+A Book Award winner Dave McKean's first creator-owned character is a wandering spirit for our times.